New methodologies for catalysis and combinatorial chemistry - Frauenlob, Robin (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
The enantioselective synthesis of chiral molecules, such as those required by the pharmaceutical industry, is one of the most important tasks in chemistry. Asymmetric catalysis is an attractive way to synthesise enantiopure compounds. Thus, the synthesis of chiral ligands has shown a great interest. Catalytic methods for the generation of enantiomerically pure compounds traditionally can be a difficult and time consuming process. The selectivity of a reaction depends not only on the catalyst but also on the substrate, which makes the quest of finding a catalyst for a specific substrate harder.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.